2012
DOI: 10.1186/1476-0711-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Enteric alpha defensins in norm and pathology

Abstract: Microbes living in the mammalian gut exist in constant contact with immunity system that prevents infection and maintains homeostasis. Enteric alpha defensins play an important role in regulation of bacterial colonization of the gut, as well as in activation of pro- and anti-inflammatory responses of the adaptive immune system cells in lamina propria. This review summarizes currently available data on functions of mammalian enteric alpha defensins in the immune defense and changes in their secretion in intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 100 publications
(67 reference statements)
6
37
0
Order By: Relevance
“…Our data also suggest that Caco-2 cells can cleave pro-HD5 into active forms. This is in line with previous reports that colon cancers express proteases capable of cleaving HD5 (14,15).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our data also suggest that Caco-2 cells can cleave pro-HD5 into active forms. This is in line with previous reports that colon cancers express proteases capable of cleaving HD5 (14,15).…”
Section: Resultssupporting
confidence: 93%
“…The expression of HD5 mRNA and protein in colon cancer has been reported previously (14,15). In our study, we demonstrate the presence of processed HD5 peptides in epithelial ovarian cancer, predominantly in cases of endometrioid cancer.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, it was reported that Prochlorperazine (ZINC19796018), an antipsychotic drug with MCS Tanimoto similarity of 0.8276 with Trifluoperazine dihydrochloride (ZINC19418959), also possesses antibacterial activity against several species [39]. Similar studies show evidence that statins, including Rosuvastatin calcium (ZINC01535101), also present activity against a range of bacterial species [40,41]. Proglumetacin maleate (ZINC85537089) belongs to the acetic acid derivatives and related substances class.…”
Section: Resultsmentioning
confidence: 99%